Model Fasies Batuan Karbonat Formasi Wainukendi di Cekungan Biak-Yapen, Papua - Permana, Asep Kurnia; Shima, Joshua; Maryanto, Sigit; Wahyudiono, Joko (Pusat Survei Geologi, 2019)
This paper provides the carbonate rocks facies model of the Wainukendi Formation. Several outcrops are well exposed in the Southern part of the Supiori Island. The main data are taken from 28 outcrops and 25 measured sections. Thirty seven rocks samples from the Korido dan Warvey Sections were collected and have been petrographic examination for microfacies analysis. Finally, the analysis find that the Wainukendi Formation basically composed by bioclastic carbonate platform and reef margin platform. Microfacies analysis indicate that these carbonate platforms consist of 4 facies zone, deep shelf (FZ2), toe of slope (FZ3), slope (FZ4), and platform margin (FZ5). Keywords: Facies, stratigraphy, Wainukendi Formation, Biak-Yapen Basin.